Increasing Children's Interest in Reading and Writing through Picture Card Teaching Aids at RAM NU 168 Al Istiqomah Gresik - Himatul Aliyah; Ida Faridah (Indonesian Journal of Education and Social Humanities, 2025)
This study aims to increase interest in reading and writing in B1 children at RAM NU 168 Al Istiqomah Gresik. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were class B children of RAM NU 168 Al Istiqomah Rejodadi Campurejo Panceng Gresik with a total of 19 children, 8 boys and 11 girls. The data of this study were obtained by being carried out through 2 cycles by observing the activeness and interest of children in reading and writing during the activity, an increase in interest in reading and writing is indicated by the achievement of an average indicator exceeding 75%. The results of the study showed that picture cards can increase children's interest in reading and writing, as evidenced by the average indicator increasing, reaching 85%. Thus, in order to increase children's interest in reading and writing, it is recommended that kindergarten teachers use picture cards and conduct further research to perfect this study.